2016
DOI: 10.1007/s12144-016-9422-6
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive? from Time to Time… Uncovering the Complex Associations between Time Perspectives and Aggression

Abstract: The aim of this study was to empirically verify a series of hypotheses on the role of time perspective (TP) in predicting aggression, formulated on the basis of TP Theory and models of aggression. Three hundred participants completed the Zimbardo Time Perspective Inventory (ZTPI) and the Aggression Questionnaire (AQ). Analysis revealed numerous significant relationships between TP dimensions and aggression. In particular, individuals scoring high on Past Negative, Present Fatalistic, and Present Hedonistic wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…Furthermore, analyses conducted within a novel concept of temporal metacognition showed that Past-Positive is positively related to each of the three distinguished aspects of temporal metacognition (Stolarski & Witowska, in press; see section 6.1.2). Finally, recent research showed that Past-Positive may attenuate the maladaptive effects of Past-Negative on aggression (Stolarski, Zajenkowski, & Zajenkowska, 2016). The latter two results provide further support for a notable role of Past-Positive in fundamental self-regulation processes.…”
Section: Past-positivesupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, analyses conducted within a novel concept of temporal metacognition showed that Past-Positive is positively related to each of the three distinguished aspects of temporal metacognition (Stolarski & Witowska, in press; see section 6.1.2). Finally, recent research showed that Past-Positive may attenuate the maladaptive effects of Past-Negative on aggression (Stolarski, Zajenkowski, & Zajenkowska, 2016). The latter two results provide further support for a notable role of Past-Positive in fundamental self-regulation processes.…”
Section: Past-positivesupporting
confidence: 56%
“…This issue was further investigated by Zajenkowski, Witowska, Maciantowicz, and Malesza (2016) who showed that Past-Negative is associated with vulnerable narcissism, but not with grandiose narcissism. Some interesting insights regarding a rather complex nature of Past-Negative come from research on aggression (Stolarski, Zajenkowski, & Zajenkowska, 2016). In their study, Past-Negative was related to verbal aggression, however after including two mediators from the emotional level (i.e., anger and hostility) the direction of this association reversed from positive to negative, revealing that beside clearly active components, expressed in elevated anger or impulsivity, Past-Negative also has a passive, depressive component that may even inhibit some negative behavioral tendencies.…”
Section: Past-negativementioning
confidence: 99%
“…In a 2016 study, Stolarski et al administered the Zimbardo Time Perspective Inventory (ZTPI) as well as the Aggression Questionnaire to 300 individuals and found that individuals with Present Hedonistic perspective were more likely to show aggressive and impulsive tendencies 63. The study did not assess for ADHD symptoms, but it would most likely yield similar results with ADHD being linked to both Present Hedonism and aggression.…”
Section: Correspondence In Lifestyles Of Adhd and Present Hedonistic mentioning
confidence: 99%
“…For example, Henik and Domino published an article entitled, “alterations in future time perspective in heroin addicts.”74 “Excessive players” and pathological gamblers’ time perspective and the possible therapeutic uses thereof are mentioned in the reports of Hodgins and Engel75 and Lukavska 76. Finally, irrespective of diagnoses, Stolarski et al63 point out the significance of balanced time perspective for a general satisfaction with life.…”
Section: Time Perspective Paradigm As a Potential Diagnostic And Thermentioning
confidence: 99%
“…A balanced time perspective (i.e., low past negative, high past positive, low present hedonistic, and high future; Zimbardo & Boyd, 2008, Stolarski, Bitner, & Zimbardo, 2011) is suggested as necessary for the experience of well-being and optimal societal functioning (Sailer, Rosenberg, Nima, Gamble, Gärling, Archer, & Garcia, 2014;Garcia, Sailer, Nima & Archer, 2016;Boniwell & Zimbardo, 2004;Stolarski, Wiberg, & Osin, 2015;Dunkel & Weber, 2010;Figueira & Bártolo-Ribeiro, 2013;Drake, Duncan, Sutherland, Abernethy & Henry, 2008;Boniwell, Osin, Linley & Ivanchenko, 2010;Stolarski, Bitner & Zimbardo, 2011;Vowinckel, Westerhof, Bohlmeijer, & Webster, 2015;Webster, 2011). For instance, time perspective or the way in which individuals anchor events and experiences in time to make sense of them is predictive of their life satisfaction (Garcia, Sailer, Al Nima, & Archer, 2016;Sailer et al, 2014), use of drugs, alcohol and tobacco (Keough, Zimbardo & Boyd, 1999), risky driving (Zimbardo, Keough, & Boyd, 1997), and aggression (Stolarski, Zajenkowski, & Zajenkowska, 2016).…”
Section: Introductionmentioning
confidence: 99%